Machine learning approach detects DDoS attacks - Son, Doan Trung; Tram, Nguyen Thi Khanh; Thu, Tran Thi (Journal of Science and Technology on Information security, 2022)
Abstract— Denial of Service attacks have been around since the dawn of the internet age. Along with the development and explosion of the Internet, denial of service attacks are also increasingly powerful and become a serious threat in cyberspace. The article aims to evaluate machine learning algorithms: K-nearest neighbor (KNN) algorithm, Decision Tree, Random Forest algorithm and Support Vector Machine (SVM) on various metrics in detecting DDoS attacks. The main objective of the paper is to analyze the algorithms, collect data and evaluate the effectiveness of the algorithms in DDoS attack detection.